Efficacy and safety of fenofibrate add-on therapy in patients with primary biliary cholangitis refractory to ursodeoxycholic acid: A retrospective study and updated meta-analysis - Guoyun, Xuan; Dawei, Ding; Ning, Liu; Yinan, Hu; Fangfang, Yang; Siyuan, Tian; Hao, Sun; Jiaqi, Yang; Ang, Xu; Guanya, Guo; Xi, Chen; Yulong, Shang; et al. (Frontiers in Pharmacology, 2022)
Abstract: Background: Ursodeoxycholic acid (UDCA) is currently used for the treatment of primary biliary cholangitis (PBC), but some people do not respond well to UDCA. Some studies have shown that the combination of fenofibrate and UDCA can improve the clinical indices in these patients. However, more high-quality evidence regarding the value of fenofibrate as a second-line therapeutic drug is needed. Methods: Through meta-analysis and a retrospective cohort study, biochemical and clinical indicator changes in UDCA-refractory PBC patients receiving combination therapy were analyzed. Then, we explored the influence of fenofibrate dose and the effectiveness and safety of long-term application. Results: Our meta-analysis included 9 publications with a total of 395 patients, including 218 treated with UDCA alone and 177 who received combination therapy. The meta-analysis showed that combination therapy was more effective than UDCA monotherapy in decreasing biochemical parameters, such as ALP, GGT, IgM, and TG. However, the occurrence of pruritus and adverse events was slightly higher with combination therapy than with UDCA monotherapy. A total of 156 patients were included in our clinical study: 68 patients underwent UDCA monotherapy, and 88 patients underwent combination therapy. Among UDCA-refractory patients, fenofibrate add-on therapy for 60 months significantly improved the ALP normalization rate. Conclusion: Our integrated analysis confirms the efficacy and safety of fenofibrate combined with UDCA in the treatment of UDCA-refractory PBC and suggests the advantages and application value of fenofibrate at a dosage of 200 mg per day. The efficacy and safety of long-term combination therapy were also confirmed in our clinical study.